FROM MATERIAL TO RELATIONAL: WHAT MOOD AND TRANSITIVITY REVEAL ABOUT EFL STUDENTS’ RECOUNT AND REPORT WRITING - Fannisa Wanda Salaras; Yanty Wirza; Wawan Gunawan (STAI Darul Qalam Tangerang, 2025)
This study explores the realization of mood and transitivity systems in Indonesian EFL students’ recount and report writings using the framework of Systemic Functional Linguistics (SFL). The study aims to describe the grammatical patterns that characterize each genre and to identify how students use language to construct meaning. The data were obtained from ten texts written by five eleventh-grade students of a vocational high school in Bandung, consisting of five recounts and five reports. Each text was analyzed clause by clause to identify mood types, process types, and thematic structures. The findings reveal that declarative clauses dominate both genres, showing that students primarily use language to provide information. In recount texts, material processes are most frequent, representing sequences of actions and events, whereas report texts are dominated by relational processes, expressing classification and description. Thematic analysis also shows that topical themes are frequently used to maintain coherence. These results indicate that students’ grammatical choices are consistent with genre purposes, yet their variation in clause construction remains limited. The study suggests that explicit teaching of SFL-based writing can enhance learners’ awareness of how language functions to convey meaning in different text types.